Incidence of rust disease (Puccinia polysora Underw.) on Manado Kuning maize (Zea mays L.) in West Langowan District - Christian Christhopher Sambur; Arthur G. Pinaria; Bernadeth Vivi Montong (Sam Ratulangi University, 2023)
Disease incidence of leaf rust disease in Manado Kuning maize is strongly influenced by the environment, that is temperature and humidity. The development of this disease can also occur in every planting season of Manado Kuning corn in West Langowan District. The direction of the wind greatly affects the spread of this disease so that this disease still exists in the Manado Kuning corn plantation in West Langowan District. The purpose of this study was to determine the incidence of rust disease in Manado Kuning corn plants in West Langowan District. This research took place in October 2022. The research was conducted using a survey method using purposive sampling. By using diagonal sampling on five plots of 2x2m square in each sample garden. Followed by observations at the Laboratory of Plant Diseases, Faculty of Agriculture, University of Sam Ratulangi Manado for microscopic observations of the morphology of urediospores. The results of this study showed the percentage of attacks was 91.2% in Langowan Barat District which was distributed in eight villages namely Noongan I Village 80.5%, Noongan III Village 88.9%, South Raringis Village 94.1%, Ampreng Village 92.3%, Tumaratas Village 94.8%, Kopiwangker Village 97.03 %, Walewangko Village 90.7%, and Raranon Village 91.3%. Keywords: Corn, Incidence, Puccinia polysora. Abstrak Kejadian penyakit penyakit karat daun pada jagung kuning Manado sangat dipengaruhi oleh lingkungan yaitu suhu dan kelembaban. Perkembangan penyakit ini juga dapat terjadi pada setiap musim tanam jagung Manado Kuning di Kabupaten Langowan Barat. Arah angin sangat mempengaruhi penyebaran penyakit ini sehingga penyakit ini masih ada di perkebunan jagung Manado Kuning di Kecamatan Langowan Barat. Tujuan dari penelitian ini adalah untuk mengetahui kejadian penyakit karat pada tanaman jagung Manado Kuning di Kecamatan Langowan Barat. Penelitian ini dilaksanakan pada bulan Oktober 2022. Penelitian dilakukan dengan metode survei dengan menggunakan purposive sampling. Dengan pengambilan sampel secara diagonal pada lima petak berukuran 2x2m persegi pada setiap kebun sampel. Dilanjutkan dengan pengamatan di Laboratorium Penyakit Tumbuhan Fakultas Pertanian Universitas Sam Ratulangi Manado untuk pengamatan mikroskopis morfologi urediospora. Hasil penelitian ini menunjukkan persentase serangan sebesar 91,2% di Kecamatan Langowan Barat yang tersebar di delapan desa yaitu Desa Noongan I 80,5%, Desa Noongan III 88,9%, Desa Raringis Selatan 94,1%, Desa Ampreng 92,3%, Desa Tumaratas 94,8%. %, Desa Kopiwangker 97,03%, Desa Walewangko 90,7%, dan Desa Raranon 91,3%. Kata Kunci: Jagung, Insidens, Puccinia polysora.